Beyond the Boundaries of Disease—Significant Post-traumatic Growth in Multiple Sclerosis Patients and Caregivers - Gil-González, Irene; Pérez-San-Gregorio, María Ángeles; Conrad, Rupert; Martín-Rodríguez, Agustín (Frontiers in Psychology, 2022)
Despite the negative repercussions of a chronic disease, multiple sclerosis (MS) might also lead to positive consequences. This longitudinal study explored post-traumatic growth in MS patients and attempted to identify possible determinants. Post-traumatic growth of 260 patients and their caregivers was compared. A subset of 209 patients and caregivers were evaluated at baseline. Patients filled in the Posttraumatic Growth Inventory and General Health Questionnaire (GHQ-28) at three different times over a 36-month follow-up period. Patient post-traumatic growth significantly increased over the follow-up period (p<0.001) with large effect sizes on almost every subscale. Higher score on the Expanded Disability Status Scale (EDSS), higher pain severity, female gender, and higher anxiety were positive predictors of post-traumatic growth, while more interference of pain, higher level of education, and more social dysfunction were negative predictors. Post-traumatic growth did not differ significantly between patients and caregivers. Our results showed significant positive intrapsychic changes of MS patients over a 36-month follow-up period up to 12 years from diagnosis. The potential influence of clinical, demographic, and mental health variables underlines the need for a personalized approach to be able to understand and sustain these processes. Comparable post-traumatic growth levels in patient-caregiver dyads at baseline suggest interdependently driven cognitive processes stabilizing well-being. Future research is recommended for further insight into the underlying cognitive processes.